PENGARUH UNSUR MAGNESIUM DAN HEAT TREATMENT PADA PERFORMA PISTON DARI VELG ALUMINIUM DENGAN ADC 12 - Amin Hakim Nur Ulya; Budi Harjanto; Nyenyep Sriwardani (Nozel : Jurnal Pendididikan Teknik Mesin, 2020)
Aluminum alloy is one of the non ferrous metals that are widely used in various fields of life including one of the automotive industry. In Indonesia, the automotive industry is currently experiencing rapid development, as indicated by the number of motorized vehicles.there are many aluminium scrap from velg those are not used intensively, so casting is done through the use of aluminium velg. To prevent damage to the piston and to approach the standard, its hardness needs to be increased, namely by adding magnesium by 0.3% and 0.6% as well as artificial aging heat treatment method at a temperature of 155 ˚C with a variation of holding time used are 2 hours and 4 hours. The original piston has a hardness value 87.5 VHN. It turns out that aluminum velg material has a chemical composition of silicon element (Si) of 12.9% which is not in accordance with the A333.0 standard, so it is necessary to add the ADC 12 in casting to make new piston material. Based on the A333.0 standard, the suitable composition is 75% ADC 12 + 25% aluminum velg with a hardness value is 83.2 VHN, but still below from the original piston hardness. After the addition of magnesium and artificial aging the hardness of the new piston material has increased. The hardness of the material is 75% ADC 12 + 25% aluminum velg which has a hardness over the original piston is a material with artificial aging 4 hours with a hardness value is 87.6 VHN, material with the addition of magnesium elements 0.3% and 0.6% as well as artificial aging 4 hours which had a violence value are 88.6 VHN and 90.2 VHN. The process of adding magnesium and artificial aging also affects the metallography of the material, namely the structure and shape of the microstructure becomes more organized and there is a change in grain size.